Eight-week treatment with sofosbuvir/velpatasvir may be effective in curing hepatitis C in children - Pokorska-Śpiewak, Maria; Dobrzeniecka, Anna; Marczyńska, Magdalena (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Sofosbuvir/velpatasvir (SOF/VEL) is a safe and effective regimen used for the treatment of chronic hepatitis C. The standard treatment duration is 12 weeks. There are no data available to support the shortened treatment. We aimed to present a case of an 11-year-old boy treated with a generic SOF/VEL for 8 weeks. The patient was admitted to our department 12 weeks after the end of treatment to establish the efficacy of the therapy (sustained virological response, SVR12). Laboratory testing revealed aminotransferases and bilirubin levels within the normal ranges, there were no abnormalities in the abdomen ultrasound, and transient elastography did not reveal any liver fibrosis. Hepatitis C virus (HCV) RNA tested with reverse-transcription polymerase chain reaction method was undetectable. The patient achieved SVR12. We conclude that shortening treatment with SOF/VEL to 8 weeks may be effective for HCV elimination in children. The possibility of treatment shortening should be confirmed in further studies on larger groups of paediatric patients.